Co-detection of respiratory pathogens in children with Mycoplasma pneumoniae pneumonia: a multicenter study - Dong, Xiaoyan; Li, Rui; Zou, Yingxue; Chen, Lina; Zhang, Hailin; Lyu, Fangfang; Yang, Wenhao; Niu, Yanhua; Wang, Haojie; Guo, Run; Wang, Xu; Li, Li; et al. (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the prevalence and clinical significance of respiratory pathogen co-detection in children diagnosed with Mycoplasma pneumoniae pneumonia (MPP).MethodsA prospective observational multicenter study was conducted, collecting clinical data from pediatric patients diagnosed with MPP in four hospitals across China from December 1 to December 31, 2023. Targeted next-generation sequencing (tNGS) results and clinical characteristics were analyzed. Participants were divided into mild and severe groups according to disease severity. Severe cases were further subdivided into an MP alone group and a multi-pathogen co-detection group. Receiver operating characteristic (ROC) curve analysis was performed to assess the predictive performance of inflammatory biomarkers for multi-pathogen co-detection.ResultsA total of 266 children were enrolled. Severe cases had significantly higher C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), lactate dehydrogenase (LDH), D-dimer, interleukin-6 (IL-6), IL-10, and interferon-γ (IFN-γ) levels, as well as longer hospital stays (all P < 0.05). Multi-pathogen co-detection was found in 49.62% of MPP patients, and was more frequent in severe cases than in mild cases (54.05% vs. 39.51%, P < 0.05). The most common co-detected pathogens were rhinovirus, adenovirus, influenza A virus, Haemophilus influenzae, and Streptococcus pneumoniae. Among severe cases, the white blood cell (WBC) count and LDH, IL-6, and IL-10 levels were significantly higher in the multi-pathogen co-detection group compared to the MP alone group (P < 0.05).ROC analysis revealed that IL-6 and IL-10, especially in combination, effectively predicted multi-pathogen co-detection.ConclusionsMulti-pathogen co-infections substantially influence the severity of pediatric MPP. The findings highlight the diagnostic value of tNGS for identifying co-pathogens and underscore the predictive potential of inflammatory biomarkers (especially IL-6 and IL-10). The integration of tNGS and these biomarkers may facilitate early detection and targeted therapeutic interventions, thereby improving prevention and treatment outcomes in pediatric MPP.